The Handling Impact Of Foreigners Seeking Protection According To Australian Policies And Its Impact On Indonesia - Faridh Al Wajidi; M. Alvi Syahrin (Journal of Law and Border Protection, 2019)
The existence of a conflict that occurs in a country makes the citizens of the country feel uncomfortable with their country so that some of them decide to run for protection. The flight has an influence on the State of Australia because it is one of the countries that are the destination countries for Asylum Seekers and so on. This then made the State of Australia make a policy in terms of maintaining sovereignty and fighting human rights crimes such as trafficking and people smuggling. The policy is Operation Sovereign Borders which turns out to experience a conflict harvest because it is not in accordance with the requirements of international law. The ratification of this policy aims at how to handle protection seekers in accordance with the requirements of International Law and law enforcement in the event of a violation based on the Operation Sovereign Borders policy. Writing KTI uses the normative juridical method. The specifications used are descriptive-analytic. Then the data used is secondary data. In its implementation, Operation Sovereign Borders is still inappropriate so that it violates the sovereignty of the Republic of Indonesia and violates the ethics of neighboring countries (good neighborliness), besides that it also violates the principles of international law contained in the 1952 Convention and instruments of International Human Rights (non-refoulement principle)